Features of the Use of Mind-Numbing Didactic Games in Primary School - qizi, Ibragimova Sitora Fakhriddin (European Journal of Life Safety and Stability (2660-9630), 2022)
Development of student’s mental abilities trough the use of age specific and educational didactic games in primary school.